2014
DOI: 10.1136/bmjopen-2013-004360
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of essential surgical capacity in Somalia

Abstract: ObjectiveTo assess life-saving and disability-preventing surgical services (including emergency, trauma, obstetrics, anaesthesia) of health facilities in Somalia and to assist in the planning of strategies for strengthening surgical care systems.DesignCross-sectional survey.SettingHealth facilities in all 3 administrative zones of Somalia; northwest Somalia (NWS), known as Somaliland; northeast Somalia (NES), known as Puntland; and south/central Somalia (SCS).Participants14 health facilities.MeasuresThe WHO To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 17 publications
4
35
0
Order By: Relevance
“…Adequate surgical equipment is vital for the provision of safe surgical care. Shortages of surgical equipment have been found in previous studies from Nigeria, Cameroon, Sierra Leone, Somalia, Ethiopia and Malawi. To ensure that surgical equipment is available, a system supporting the equipment needs to be in place so that the right equipment is procured, used and maintained as intended, following appropriate training along with a secure supply chain of consumables.…”
Section: Introductionsupporting
confidence: 52%
“…Adequate surgical equipment is vital for the provision of safe surgical care. Shortages of surgical equipment have been found in previous studies from Nigeria, Cameroon, Sierra Leone, Somalia, Ethiopia and Malawi. To ensure that surgical equipment is available, a system supporting the equipment needs to be in place so that the right equipment is procured, used and maintained as intended, following appropriate training along with a secure supply chain of consumables.…”
Section: Introductionsupporting
confidence: 52%
“…Of these, 19 reports described water availability at hospitals in a LMIC ( Figure 1). 23,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47] LMICs with at least one report of water availability spanned 5 continents: Africa (11 reports; 58% of reports); Asia (4; 21%); South America (2; 11%); North and Central America (1; 5%); and Oceania (1; 5%). Reports from 3 countries, Afghanistan, Somalia, and Ghana, did not include hospital-specific data regarding water availability.…”
Section: Search Resultsmentioning
confidence: 99%
“…The global volume of surgery is more than 200 million surgical procedures per year, and there is significant inequality between procedures performed in high-income and low-income countries (12,24). It has been reported that, of the 243 million surgical procedures performed globally each year, 34.8% of the world's population living in low-income countries only has access to 8.1 million (3.5%) of such procedures (25,26). Of these procedures, only a quarter are performed in low-and middle-income countries where nearly three-quarters of the world's population lives.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical programs at WHO are rapidly evolving due to increasing awareness of the fact that surgical conditions are important public health problems, and also due to realizing that surgery is an efficacious and cost-effective field of health services (23). Improving access to surgical care in low-income countries requires addressing paucities in training and skills of personnel, appropriate equipment, medications, and infrastructure (26).…”
Section: Surgical Diagnosesmentioning
confidence: 99%